Stress change generated by the 2019 İstanbul–Silivri earthquakes along the complex structure of the North Anatolian Fault in the Marmara Sea - Murat Şahin; Cenk Yaltırak; Fatih Bulut; Aslı Garagon (Earth, Planets and Space, 2022)
Abstract The North Anatolian Fault Zone is a dextral system operating between the Eurasian and Anatolian plates in northern Turkey. Across the Marmara Sea south of İstanbul, it deforms at ~18 mm/year slip rate, where the statistics of historical earthquakes suggest that a few M7+ earthquakes are generated every ~250 years. Currently, M7+ earthquakes are overdue as this section of the fault has not been reactivated since the 1766 and 1754 earthquakes. In this frame, identifying the stress change by the 2019 M5.8 İstanbul–Silivri earthquake is essential to characterize its influence on the critically stressed Marmara Sea segments of the North Anatolian Fault Zone. To do this, we mapped not only the main segments but also the secondary faults in the vicinity of the 2019 M5.8 İstanbul–Silivri earthquake to locate the fault patch it reactivated, as well as to accurately model the fault segments, where it significantly changed the stress. The joint analysis of relocated hypocenters and the Coulomb stress modeling shows that the mainshock failed a SW–NE striking splay fault, generating a stress increase of up to three bars on the fault that has the potential to generate M7+ earthquake. Graphical Abstract